Discovery of protease inhibitors from bacteria as novel adjuvants for oral vaccine formulations - Coria, Lorena M.; Pueblas Castro, Celeste; Bruno, Laura; Nakaya, Helder I.; Pasquevich, Karina A.; Cassataro, Juliana (Frontiers in Immunology, 2025)
IntroductionThere is a need for mucosal vaccines that can fight pathogens at the site of infection. At present, there are no approved adjuvants for mucosal vaccines. Among different immunization routes, oral delivery is the natural choice because of its ease of administration. However, oral administration has two main drawbacks: proteolytic digestion and immune tolerance.MethodsIn this study, a systematic in silico screening of putative protease inhibitors (PIs) from bacteria to identify novel oral vaccine adjuvants was conducted. Selected candidates were then evaluated for their ability to inhibit gastrointestinal proteases and to stimulate murine dendritic cells. Finally, promising candidates were incorporated as adjuvants into oral vaccine formulations containing model (OVA) or real antigens, such as the cholera toxin B subunit (CTB) and tetanus toxoid and tested in in vivo experiments. In addition, a proteomic analysis to assess their effects on dendritic cells was performed.ResultsThis approach led to the selection of 11 PIs from human pathogenic bacteria, representing diverse families of PIs. These proteins were then expressed in E. coli; five of them demonstrated soluble expression and efficient purification. Three candidates -Ecotin from Salmonella, APRin from Pseudomonas, and STA (staphostatin A) from Staphylococcus aureus- exhibited both protease inhibition and TLR4-independent dendritic-cell activation. In vivo studies demonstrated that Ecotin, APRin, and STA enhanced immune responses when orally co-administered with OVA, promoting T-cell proliferation and antibody production. Further evaluation with real antigens, confirmed their adjuvant effect by inducing mucosal and systemic immunity. Proteomic analysis of dendritic cells treated with these proteins revealed significant enrichment in immune-related pathways, including interferon and TNF-signaling, as well as metabolic pathways linked to immune activation.ConclusionsThese results demonstrate that three protease inhibitors from bacteria: Ecotin, APRin, and STA function as novel oral mucosal adjuvants capable of modulating immune responses and enhancing antigen immunogenicity.